2001
DOI: 10.1097/00006123-200110000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Resolution of Residual Hemifacial Spasm after Microvascular Decompression Operations

Abstract: Approximately 50% of patients with HFS exhibited residual spasm postoperatively. An immediate postoperative silent period of 4 days without spasm was characteristic. One-quarter, one-half, and 90% of the residual spasm resolved by 1 week, 1 month, and 8 months after surgery, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 20 publications
1
28
1
1
Order By: Relevance
“…We repetitively found late effect of MVD amongst our patients. Ishiakawa et al [30] were the first to describe the postoperative course in detail after MVD. In their study, approximately 50% of all patients who underwent MVD had some degree of postoperative HFS.…”
Section: Discussionmentioning
confidence: 99%
“…We repetitively found late effect of MVD amongst our patients. Ishiakawa et al [30] were the first to describe the postoperative course in detail after MVD. In their study, approximately 50% of all patients who underwent MVD had some degree of postoperative HFS.…”
Section: Discussionmentioning
confidence: 99%
“…Ishikawa et al reported that 90% of patients with residual post-operative spasm had resolution of their symptoms within 8 months. 15 In addition, Gotu et al described immediate cure following MVD in 76.5% of cases, and a 91.6% cure rate at 1 year. 16 Shin et al achieved an ''excellent'' result in 61.1% of patients 1 week after MVD, and in 82.7% of patients 6 months after MVD.…”
Section: Discussionmentioning
confidence: 99%
“…At this time point, HFS was abolished in five patients in whom LSRs persisted at the end of surgery. However, HFS can recur or disappear several months after MVD,27 28 and so the immediate postoperative result does not always reflect the long-term outcome. Actually, we found that the absence of LSRs at the end of surgery correlated to MVD efficacy in the long term.…”
Section: Discussionmentioning
confidence: 99%